Analisis Kebijakan Kenaikan Jabatan Fungsional Guru dan Angka Kredit dari IV a ke IV b - Imam Subarkah (LPPM IAINU Kebumen, 2020)
One of the successes of education is determined by the role of the teacher, so that the government needs active attention to motivate them to carry out higher educational responsibilities. One of the factors that can increase the motivation of teachers to work by the government is the active facilitation of their career development. The government needs to actively facilitate the promotion of teacher functional positions and credit scores from IV/a to IV/b to various opportunities in their career development. It is hoped that this will give birth to educators who have a strong motivation in improving their professionalism, so that the quality of education can continue to be improved. This study shows that the provision of technical facilities in increasing the number of teachers with rank IV/a to rank IV/b. Simplification of the mechanism for proposing promotions through the online system and efforts to establish cooperation with tertiary institutions in the regions in producing scientific work is important in order to increase the number of teachers with rank and grade IV/b.